Applying nanotechnology for environmental sustainability - Joo, Sung Hee (Advances in environmental engineering and green technologies (AEEGT) book series, 2017)
This book addresses the applications of nanomaterials in the field of environmental conservation and sustainability, and analyzes the potential risks associated with their use